2004
DOI: 10.1007/s00421-004-1262-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of back muscle endurance, maximum force, balance and trunk rotation control regarding lifting capacity

Abstract: Evaluation of lifting capacity is widely used as a reliable instrument in order to evaluate maximal and safe lifting capacity. This is of importance in regard to planning rehabilitation programs and determining working ability. The aim of this study was to investigate the influence of basic functions on the lifting capacity measured by the progressive isoinertial lifting evaluation (PILE) and the functional capacity evaluation (FCE) tests in a lower (floor to waist) and an upper (waist to shoulder) setting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…In most studies, about three MVC are measured at short periods intervals; sometimes additional trials are permitted and the best result of the contractions is selected (Demoulin et al, 2006a;Schenk et al, 2006).…”
Section: Static Strength Testmentioning
confidence: 99%
“…In most studies, about three MVC are measured at short periods intervals; sometimes additional trials are permitted and the best result of the contractions is selected (Demoulin et al, 2006a;Schenk et al, 2006).…”
Section: Static Strength Testmentioning
confidence: 99%
“…This is supported by the suggestion of Nussbaum and Lang (2005) that relative joint demands may determine MAWL and the relation found between back muscle activity levels and decisions to modify weights during tests of MAWL (Jorgensen et al 1999, Davis et al 2000. On the other hand, Schenk et al (2006) found that only 18-19% of the variance in MAWL, assessed using a functional capacity evaluating (FCE) lifting test, could be accounted for by basic capacities such as strength and endurance of the trunk muscles. Although trunk capacity partially explained MAWL, several uncertainties remain, including the effect of differences in lifting technique.…”
Section: Introductionmentioning
confidence: 69%
“…Schenk et al (2006) determined that the abdominal muscles contribute to the stabilisation of the lumbar spine in both lateral and frontal positions when lifting objects. Thus, without sufficient abdominal strength one can expect that the individual is likely to develop lower back pain and as a consequence the person becomes less mobile and less functional.…”
Section: Physical Tests In Relation To the Functional Tasksmentioning
confidence: 99%
“…It has already been highlighted that adequate abdominal strength elicits high performance scores on general ability tasks, as well as provide stabilisation of the lumbar spine for many essential basic activities such as lifting, pulling and pushing (Michaelides et al, 2009;Schenk et al, 2006). Levinger et al (2007) showed that resistance training which included abdominal training, improved the capacity to perform ADL and this result was independent of changes in body fat or aerobic power.…”
Section: Modified Curl Upmentioning
confidence: 99%